Ali Cross - Patterson, James (London Young Arrow, 2020)
Alex Cross, the brilliant DC detective who never gives up on a case. Ali Cross, the tenacious kid who's determined to follow in his father's footsteps. The case that finally gives him a chance Ali knows Gabe Qualls better than anyone, so when his friend goes missing, Ali jumps right into action. Being Alex Cross's son has taught him the skills he needs to solve the mystery- intelligence, persistence, and logic. One thing he didn't inherit? Patience. Because Ali knows that with every day that passes without the police finding Gabe, the less likely it is that he'll ever be found. And being Alex Cross's son, he refuses to accept those odds.
Keywords: Children of police -- Juvenile fiction -- Child detectives -- Juvenile fiction -- Washington (D.C.) -- Detective and mystery stories